2017
DOI: 10.1155/2017/1857580
|View full text |Cite
|
Sign up to set email alerts
|

Integrating miRNA and mRNA Expression Profiling Uncovers miRNAs Underlying Fat Deposition in Sheep

Abstract: MicroRNAs (miRNAs) are endogenous, noncoding RNAs that regulate various biological processes including adipogenesis and fat metabolism. Here, we adopted a deep sequencing approach to determine the identity and abundance of miRNAs involved in fat deposition in adipose tissues from fat-tailed (Kazakhstan sheep, KS) and thin-tailed (Tibetan sheep, TS) sheep breeds. By comparing HiSeq data of these two breeds, 539 miRNAs were shared in both breeds, whereas 179 and 97 miRNAs were uniquely expressed in KS and TS, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…STHS have a high reproductive capacity and show polyembryony; they grow fast and could be in oestrum at all seasons ( Kashan et al, 2005 ). TS are raised in the mountainous region of the Qingzang plateau, where the average elevation is 3,500 m. Compared with LFTS and STHS, TS are relatively stronger and their tails are the smallest with less fat accumulation ( Zhu et al, 2016 ; Zhou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…STHS have a high reproductive capacity and show polyembryony; they grow fast and could be in oestrum at all seasons ( Kashan et al, 2005 ). TS are raised in the mountainous region of the Qingzang plateau, where the average elevation is 3,500 m. Compared with LFTS and STHS, TS are relatively stronger and their tails are the smallest with less fat accumulation ( Zhu et al, 2016 ; Zhou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study has shown that cir-cRNAs can regulate gene expression through a circRNA-miRNA-mRNA pathway [31]. Another pioneering study has demonstrated that miRNAs are differentiallyexpressed between fat-tailed and short-tailed sheep breeds [61]. However, there remains lack of research on circRNA in sheep SF at different developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…Research on IMF is extensive in farm animals, such as bovine (Harper and Pethick, 2004;Takenouchi et al, 2004;Taniguchi et al, 2008;Du et al, 2010b;Romao et al, 2011;Cardoso et al, 2012;Huang et al, 2012;Hudson et al, 2015;Guan et al, 2017;Ma et al, 2018), porcine (Hausman and Poulos, 2004;Zhang et al, 2014;Chen et al, 2018;Won et al, 2018), sheep (Dodson et al, 1997;Tong et al, 2008;Zhou et al, 2017;Pan et al, 2018) and chicken (Qiu et al, 2017;Wang et al, 2017a;Cui et al, 2018;Fu et al, 2018), and have brought to the development of a wealth of isolation, growth, characterization and differentiation protocols.…”
Section: Adipocytes and Imfmentioning
confidence: 99%